Outpatient Prescription Opioid Use following Discharge after Deep Inferior Epigastric Perforator Breast Reconstruction with and without an Educational Intervention - Marquez, Jessica L.; Chow, Josh; Moss, Whitney; Luo, Jessica; Eddington, Devin; Agarwal, Jayant P.; Kwok, Alvin C. (Journal of Reconstructive Microsurgery, 2024)
Background There is limited evidence for appropriate postoperative opioid prescribing in autologous breast reconstruction. We sought to describe postoperative outpatient prescription opioid use following discharge after deep inferior epigastric perforator (DIEP) breast reconstruction with and without an educational video.Methods Patients undergoing DIEP reconstruction were given a 28-day postoperative pain and medication logbook from August 2022 to June 2023. Our practice implemented an educational video upon discharge on proper opioid consumption. Descriptive statistics on patient characteristics, intraoperative and postoperative opioid consumption, and outpatient prescription opioid use after discharge were compared between the two cohorts.Results A total of 53 logbooks were completed with 20 patients in the no video cohort and 33 in the video cohort. On average, the days to cessation of opiates was longer in the no video cohort (8.2 vs. 5.1 days, p = 0.003). The average number of oxycodone 5 mg equivalents consumed following discharge was 13.8 in the no video cohort and 7.8 in the video cohort, which was statistically significant (p = 0.01). Overall, the percentage of opioids prescribed that were consumed in the video cohort was 28.3% versus 67.1% in the no video cohort.Conclusion For patients discharging home after DIEP reconstruction, we recommend a prescription for 12 oxycodone 5 mg tablets. With the use of an educational video regarding proper opioid consumption, we were able to reduce the total outpatient opioid use to 5 oxycodone 5 mg tablets following hospital discharge.
Keywords: opioid prescribing guidelines; breast reconstruction; postoperative opioids; postoperative pain control